The Use of Request Strategies in the Movie "The Proposal" - Desi Wulan Sari (Lexicon, 2014)
This research aims to investige the requests used in the movie The Proposal. In particular, it attempts to identify and classify the request head acts and external modification delivered by the characters in the movie. The data used in this research are utterances containing request strategies. These data, then, are classified and analyzed using the theory of request strategies proposed by Blum-Kulka and Olshtain (1984). The results show that there are 75 utterances containing request strategies, classified based on nine types of the request head acts and seven types of external modifications that modify the head acts. It is also found that direct request by means of mood derivable is the most preferred strategy in expressing request head act. Futhermore, precusors is the external modification most commonly used by the characters to get the hearer‟s attention and to fulfill something requested.